Internationalization at Harvard - Ned Strong (Laureate Education Inc, 2013)
The aim of this essay is to describe internationalization at Harvard University. Founded by European colonists in 17th century New England, Harvard has historic international roots. By the mid 1900's it had become an international powerhouse attracting top students, academics and scientists from around the world. Yet, the University is international almost by default as it has reacted to world affairs. Looking toward the future, President Drew Faust has outlined a strategy to become "intentionally global". One model, begun ten years ago, serves as an example for the future. In 2002 the University established its first overseas office designed to represent the entire institution. The theory was that a modest local infrastructure would encourage students and faculty to expand international collaborations and make a difference in the region benefiting from this presence. The results have been highly successful. The Regional Office in Santiago Chile, representing Argentina, Bolivia, Chile, Peru, and Uruguay, has catalyzed engagement of over 3000 faculty and students in the last ten years. Over 50 significant collaborative research programs have benefitted thousands of preschool children, pioneered new approaches to disaster relief, improved health care, revolutionized public housing, and led to scientific breakthroughs. This model of a small physical footprint exerting large academic influence will be one of the central strategies as Harvard looks toward the future. DOI: 10.18870/hlrc.v3i2.117